Exploring Factors Influencing the Mental Preparedness of English Pre-Service Teachers for Professional Practice: A Mixed Methods Study - Febria, Desty; Oinuma, Sachi; Zaki, Leil Badrah (JOLLT Journal of Languages and Language Teaching, 2025)
Effective teaching in various situations depends significantly on English pre-service teachers' mental readiness, impacted by motivation, self-efficacy, teaching experience, and institutional support. Qualitative and quantitative cases consider was conducted with 60 Englihs pre-service teachers from diverse backgrounds. Thematic analysis revealed that inherent motivation and practical teaching experiences are vital for adaptability and certainty. In spite of a high level of self-assurance, numerous English pre-service teachers still struggle with classroom management and adjusting to new learning settings. Roughly 60% detailed their practical teaching experiences significantly affected their planning. The study adjusts with Bandura's social cognitive theory, highlighting how behavioral, relevant, and individual variables shape availability. To reduce stress and improve self-efficacy, organization back such as support and assets is basic. The study underscores the significance of integrating professional improvement, and hands-on teaching experiences into teacher preparing programs to make strides readiness. These discoveries propose that educational module ought to address English pre-service teachers' needs, influencing both teachers and policymakers. This investigate contributes to improving teaching quality and results by cultivating key aptitudes, certainty, and procedures. It emphasizes the need to refine teacher preparation programs to superior support English pre-service teachers' mental readiness in different educational settings.